MAP kinase gene STK1 is required for hyphal, conidial, and appressorial development, toxin biosynthesis, pathogenicity, and hypertonic stress response in the plant pathogenic fungus Setosphaeria turcica - Po LI; Xiao-dong GONG; Hui JIA; Yong-shan FAN; Yun-feng ZHANG; Zhi-yan CAO; Zhi-min HAO; Jian-min HAN; Shou-qin GU; Jin-gao DONG (Journal of Integrative Agriculture)
The mitogen-activated protein kinase (MAPK), a key signal transduction component in the MAPK cascade pathway, regulates a variety of physiological activities in eukaryotes. However, little is known of the role MAPK plays in phytopathogenic fungi. In this research, we cloned the MAPK gene STK1 from the northern corn leaf blight pathogen Setosphaeria turcica and found that the gene shared high homology with the high osmolality glycerol (HOG) MAPK gene HOG1 of Saccharomyces cerevisiae. In addition, gene knockout technology was employed to investigate the function of STK1. Gene knockout mutants (KOs) were found to have altered hyphae morphology and no conidiogenesis, though they did show similar radial growth rate compared to the wild-type strain (WT). Furthermore, microscope observations indicated that STK1 KOs did not form normal appressoria at 48 h post-inoculation on a hydrophobic surface. STK1 KOs had reduced virulence, a significantly altered Helminthosporium turcicum (HT)-toxin composition, and diminished pathogenicity on the leaves of susceptible inbred corn OH43. Mycelium morphology appeared to be significantly swollen and the radial growth rates of STK1 KOs declined in comparison with WT under high osmotic stress. These results suggested that STK1 affects the hyphae development, conidiogenesis, and pathogenicity of S. turcica by regulating appressorium development and HT-toxin biosynthesis. Moreover, the gene appears to be involved in the hypertonic stress response in S. turcica.